Comparison Between Tax Amnesty, The Voluntary Disclosure Program and The Proposed 2025 Tax Amnesty: An Analysis of Legal Certainty and Tax Compliance in Indonesia - Anwar Saleh Hasibuan; Nurainun; Lidiya Putri; Reza Azurma (Journal of Creative Power and Ambition (JCPA), 2026)
Taxation is the primary source of state revenue with a strategic role in financing national development. To enhance compliance and broaden the tax base, Indonesia has implemented a Tax Amnesty policy under Law Number 11 of 2016 and a Voluntary Disclosure Program based on Law Number 7 of 2021 concerning Harmonization of Tax Regulations. However, the emergence of discourse on a third round of Tax Amnesty included in the 2025 Priority National Legislative Program raises serious debates regarding the principles of legal certainty, tax justice, and moral hazard risks. This study aims to analyze and compare the legal arrangements, policy designs, and juridical implications of the 2016 Tax Amnesty, 2022 Voluntary Disclosure Program, and the 2025 Tax Amnesty discourse. The research method used is normative legal research with statutory and comparative approaches. The results indicate an evolution of policies from an extraordinary measure towards a transitional compliance instrument linked to the implementation of the Core Tax Administration System. However, the repetition of amnesty policies potentially undermines long-term legal certainty and tax compliance if not balanced with consistent law enforcement.